Barriers and motivators for physical activity in community dwelling adults: a comprehensive systematic review. Issue 4 (December 2016) - Alexander, L.A.; Cooper, K.
Abstract : Background: Benefits of a physically active lifestyle include an increase in physical, social and mental health and well-being, and a significantly reduced risk of developing non-communicable conditions including cardiovascular disease, diabetes and obesity. However, despite these benefits not all individuals meet current international guidelines for physical activity (PA). In order to facilitate uptake and maintenance of regular physical activity, it is important to identify and understand any barriers or motivators to PA in a community setting. Therefore, we undertook a comprehensive systematic review of the barriers and motivators for physical activity in community dwelling adults. Objective: The quantitative objective was to identify the barriers and motivators for participation in physical activity in community dwelling adults. The qualitative objective was to identify the community dwelling adults' perceptions and experiences of barriers and motivators to physical activity Methods: Studies were considered if they included community dwelling adults in developed countries aged 19–64 years without any medical conditions. Studies published in English from 2004 to September 2015 that identified barriers and motivators to physical activity or perceptions and experiences of barriers and motivators were included. A three step search strategy was employed to identify relevant studies. Each study was assessed by two independent reviewers prior to inclusion in the review using the JBI-MAStARI and JBI-QARI tools. Any disagreements were resolved through discussion or with a third reviewer. Results: Electronic searches identified over 16, 000 citations of which 91 were included in the review (46 qualitative and 45 quantitative); providing data on over 72, 000 adults. Studies were undertaken internationally (UK, Europe, Australia, and Canada) with the majority occurring in the USA. Study participants represented rural and urban populations, mother/mothers to be, low income and socio-economically disadvantaged adults, overweight/obese adults as well as ethnically diverse populations with a greater number of females than males represented. The majority of the quantitative studies were descriptive in nature and due to the diverse nature of these studies; this section of the review underwent a narrative analysis and presentation. The qualitative findings were pooled together into categories to undergo a meta-synthesis to produce comprehensive synthesised findings around barriers and motivators to physical activity. Initial results identified the most commonly reported barriers were intra and inter-personal such as time, obligations, fatigue, and the most common motivators were health benefits (mental & physical), support and childcare. Results are currently being finalised and will be reported fully in this presentation. Discussion: This review has comprehensively encompassed the key barriers and motivators to physical activity in community dwelling adults and has included both quantitative and qualitative data. This has enabled us to use in-depth data from adults' perceptions as well as comprehend the frequency of specific barriers and motivators that are reported in relation to physical activity. Conclusion: This review has contributed to further understanding the barriers and motivators around physical activity in community dwelling adults. The results will support the development of interventions to address barriers to physical activity, whilst consolidating motivators that maintain and increase physical activity in community dwelling adults.